Effect Of Macroeconomic Factors (Exchange, Inflation, Sbi Interest Rate, World Oil Price) On Stock Returns With Profitability As Intervening Variables In Mining Sector Companies In The Indonesia Stock Exchange 2015-2019 - Dutiva Br. Ginting, Elsa; Matondang, Sofiyan (CV. Inara, 2022)
The purpose of this study was to determine and analyze the effect of macroeconomic factors (exchange rate, inflation, interest rates for Bank Indonesia Certificates, world oil prices) on stock returns with profitability (return on assets) as an intervening variable in mining sector companies on the Indonesia Stock Exchange in 2015 -2019. The data used in this study is secondary data obtained from monthly and annual data published by Bank Indonesia, the Indonesia Stock Exchange, and the Energy Information Administration (EIA) and processed using Path Analysis with SmartPLS 3.0. The results showed that macroeconomics (exchange rate of Rp/US, inflation, SBI interest rates, world oil prices) and ROA had a direct significant effect on stock returns in the mining sector on the Indonesia Stock Exchange (IDX). Macroeconomics (Rp/US exchange rate, inflation and world oil prices) have an indirect and significant indirect effect on Stock Return of the mining sector on the IDX, while the SBI interest rate has a significant indirect effect on Stock Return of the mining sector on the IDX.